Arabic speaking and the melting of religious and historical entities. We cannot be unified without El DhadBy Mustafa Mohammed - achori, fatiha (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
Our research paper aims to show the virtue of the Arabic language and its role over time in preserving existential entities, self-identities, national and national identities, despite the suffocating prejudices and fierce campaigns that have been encountered and continue to oppose them, in an attempt to obliterate its features and its existence, In addition to the modern tide with its various currents, which seeks to reduce it within the framework of a reactionary space, only because it is associated with religion (the Qur'an), and then within a geographical space limited to arab speakers, All of this, in their beliefs, has made it a classical language that can be understood in a historical heritage context, unable to read reality and assimilate postmodern systems, especially since it has also been taken from it as the language of spiritual entities, poetry, and feelings, more related to the heart than to the mind, Science, civilization and physical entities as a whole, but the specificity of the Arabic language at Mustafa Mohammed al-Ghomari goes beyond its general conceptual framework to an approach that stands at the controversy of religious, historical, cultural and cultural entities that do not establish boundaries between what it was , and what it is and what it will be.